2021
DOI: 10.12973/ijem.7.2.319
|View full text |Cite
|
Sign up to set email alerts
|

Problems Experienced in the Literacy Teaching Process by Foreign Students in the First Grade of Primary School

Abstract: <p style="text-align: justify;">The aim of this study is to obtain classroom teachers' views on the problems experienced in the literacy process by foreign students in the first grade of primary school, which constitutes an important part of language acquisition. A qualitative research approach has been adopted in the research. The data were obtained using a semi-structured interview form. With the semi-structured interview form created by the researchers, the opinions of the teachers working in the city… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The application PowerPoint creates a number of fascinating offers on different slide transition schemes and animations. The transitions and animations when used efficiently offers a teacher a chance to play quiz games while teaching spellings, pronunciations, coloring of letters and capitalization of letters (Kasa and Ates, 2021). The significant aspect of the animations and transitions in classroom instruction is that a teacher expected to know at what point to apply them in presenting the specific aspects of learning.…”
Section: Automated Animation and Transition Gamming Features For Inte...mentioning
confidence: 99%
“…The application PowerPoint creates a number of fascinating offers on different slide transition schemes and animations. The transitions and animations when used efficiently offers a teacher a chance to play quiz games while teaching spellings, pronunciations, coloring of letters and capitalization of letters (Kasa and Ates, 2021). The significant aspect of the animations and transitions in classroom instruction is that a teacher expected to know at what point to apply them in presenting the specific aspects of learning.…”
Section: Automated Animation and Transition Gamming Features For Inte...mentioning
confidence: 99%
“…Trough the comprehensive analysis of the above two questions, the results showed that students have a high evaluation of their understanding of AR tools and believe that AR learning tools can efectively improve their learning efciency and participation, thus helping to improve classroom autonomy [16].…”
Section: Self-perception Data Of Course Learningmentioning
confidence: 99%